Association between the stress hyperglycemia ratio and all-cause mortality in critically ill patients with T2DM: a retrospective study - Rui, Yuanyuan; Wu, Bing; Huang, Changbao; Li, Qian (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have shown a significant correlation between the stress-hyperglycemia ratio (SHR) and mortality. However, it is unknown whether the SHR has the same predictive value in severely ill patients. The main purpose of this research was to investigate the association between the SHR and all-cause mortality in critically ill patients with T2DM.MethodsThe data used in this study were derived from the Medical Information Mart for Intensive Care (MIMIC-IV) database. The primary outcome was 180-day mortality and the secondary outcomes were 28-day, 90-day and 365-day mortality. The main analytical methods included: Kaplan-Meier survival analysis, the COX proportional hazards model and restricted cubic splines.ResultsA total of 993 patients were included. The 28-day, 90-day, 180-day, and 365-day mortalities reached 10.4%, 14.4%, 16.7% and 19.0%, respectively. Multivariate Cox proportional hazards analysis revealed that the elevated SHR was significantly related to 28-day, 90-day and 180-day all-cause mortality even after cofounder adjustment. Restricted cubic spline analysis revealed a nonlinear association between the SHR and the risk of 28-day (p for nonlinear=0.014), 90-day (p for nonlinear=0.007), 180-day (p for nonlinear=0.001) and 365-day (p for nonlinear=0.003) all-cause mortality.ConclusionSHR is significantly associated with 28-day, 90-day and 180-day all-cause mortality in critically ill patients with T2DM. This may help us identify patients at higher risk of death early.